2000
DOI: 10.1042/bj3480439
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish ftz-f1 gene has two promoters, is alternatively spliced, and is expressed in digestive organs

Abstract: Fushi-tarazu Factor-1 (FTZ-F1) is a family of nuclear receptors involved in various developmental processes. We have cloned a zebrafish FTZ-F1 gene, termed ff1, which belongs to the fetoprotein transcription factor/liver receptor homologue-1 (FTF/LRH-1) subgroup of the FTZ-F1 family. Four transcripts arise as a result of differential promoter usage and alternative splicing at the 3'-most exons. The longer transcript, form A, encodes a transcriptional activator. The shorter transcript, form B, lacks the activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
4
18
0
1
Order By: Relevance
“…Alternative promoter usage has also been observed in the FF1 gene which encodes the zebrafish orthologue of mLRH-1 [17]. Together with our findings, an important question arises: does human LRH-1 gene employ a similar regulatory mechanism to produce variant(s) during embryogenesis and in some adult tissues?…”
Section: Conserved Expression Of the Novel Transcript In Ratssupporting
confidence: 79%
“…Alternative promoter usage has also been observed in the FF1 gene which encodes the zebrafish orthologue of mLRH-1 [17]. Together with our findings, an important question arises: does human LRH-1 gene employ a similar regulatory mechanism to produce variant(s) during embryogenesis and in some adult tissues?…”
Section: Conserved Expression Of the Novel Transcript In Ratssupporting
confidence: 79%
“…In mammals, expression of SF-1 is essential for the development of gonadotrope of pituitary and VMN of hypothalamus (Parker and Schimmer,'97). In fish, FTZ-F1 homologues were found, by the whole mount in situ hybridization method, to express in the pituitary gland and hypothalamus during embryogenesis in zebrafish (Chai and Chan, 2000;Lin et al, 2000;von Hofsten et al, 2001). RT-PCR analysis indicated that expression of zebrafish zFF1A started from segmentation stage (Lin et al, 2000).…”
Section: Ftz-f1 Homologue In Orange-spotted Groupermentioning
confidence: 99%
“…Within the coding region the intron–exon structure of Smftz‐f1 is conserved in relation to members of the NR5A2 family (including human FTF/LRH (accession no. NT_021968) and zebrafish ff1 [19]) and the NR5A1 family such as the mouse ELP (SF‐1) gene [56], with three of six intron positions conserved. When compared to the D. melanogaster ftz‐f1 gene (accession no. )…”
Section: Organization Of the Smftz‐f1 Gene And Alternative Promoter Umentioning
confidence: 99%